PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN JABATAN FUNGSIONAL AUDITOR TERHADAP KOMITMEN ORGANISASI DAN DAMPAKNYATERHADAP KINERJA AUDITOR INTERNAL (Studi pada BPKP dan Inspektorat Sumatera Selatan) - Handayani, Mella (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This study examines the influence of organizational commitment, organizational culture, leadership style, functional position on performance of auditors.. This research uses convenience sampling technique to select the respondent . Data were collected through a survey on 98 government auditors who work at Inspectorate of South Sumatra Province and BPKP representative of South Sumatra. Structural Equation Model (SEM) with Partial Least Square (PLS) was applied to analyzed the data. The result of this research indicate positive influence of  organizational culture, leadership style, functional position on performance of auditors. Futhermore, it was found that there were no significant influence on organizational culture, leadership style, functional position on performance of auditors with organizational commitment as antecedent